2022
DOI: 10.3389/fneur.2022.909828
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Promote the Progression of Sepsis-Induced Cardiomyopathy and Neurovascular Dysfunction Through Upregulation of NF-kappaB Signaling Pathway-Associated HDAC7/ACTN4

Abstract: IntroductionThe objective of this study was to determine the NF-kappaB pathway, hub genes, and transcription factors (TFs) in monocytes implicated in the progression of neurovascular-related sepsis-induced cardiomyopathy (SIC) as well as potential miRNAs with regulatory functions.Methods: Sepsis-induced cardiomyopathy—and heart failure (HF)-related differentially expressed genes (DEGs) between SIC and HF groups were identified separately by differential analysis. In addition, DEGs and differentially expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…The significance of NF‐κB‐related signaling pathways in various organ injuries caused by sepsis is well‐established. Numerous studies have reported the pivotal role of NF‐κB signaling pathways in the pathogenesis of organ injuries induced by sepsis (Luo et al., 2022; Wang et al., 2011; Zhang et al., 2017). When the body encounters external stimuli, it initiates innate immunity, leading to the induction of TLR4 expression and subsequently triggering an adaptive immune response.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of NF‐κB‐related signaling pathways in various organ injuries caused by sepsis is well‐established. Numerous studies have reported the pivotal role of NF‐κB signaling pathways in the pathogenesis of organ injuries induced by sepsis (Luo et al., 2022; Wang et al., 2011; Zhang et al., 2017). When the body encounters external stimuli, it initiates innate immunity, leading to the induction of TLR4 expression and subsequently triggering an adaptive immune response.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB is recognized as a key regulator of cellular in ammatory responses triggered by proin ammatory stimuli [40]. It plays a pivotal role in modulating molecular pathways associated with in ammation [41].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of uniformity suggests a multifactorial etiology, type of bacteria, or immune response. It is important to highlight that 13(43.3%) of those with myocardial dysfunction had culture negative sepsis, hence SIRS might be a possibility, or mitochondrial depletion (18)(19)(20)(21). In neonates with sepsis, the discharge of cytokines, acidosis and hypoxia may result in the advancement of pulmonary hypertension and in this way right ventricular dysfunction, whereas right-heart dysfunction will impair left-heart function (22).…”
Section: Discussionmentioning
confidence: 99%